2022
DOI: 10.3390/toxics10100627
|View full text |Cite
|
Sign up to set email alerts
|

Statins and Male Fertility: Is There a Cause for Concern?

Abstract: The well-known 3-hydroxyl 3-methyl glutaryl-Coenzyme A reductase inhibitors, called statins, have been the main medication used in the treatment of hypercholesterolemia and some cases of cardiovascular diseases. The effectiveness of this drug in controlling cholesterol production is impeccable, however, patients often complain of a variety of side effects, such as myalgia, muscle atrophy, and in some cases, rhabdomyolysis. Not only has the use of statins caused the aforementioned side effects, but they are als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 92 publications
1
3
0
Order By: Relevance
“…Our data suggested hazardous effects of atorvastatin on the reproduction system which is in line with studies conducted on rat and human which reported erectile and testicular dysfunction, altered steroid hormone production, and reducing sperms’ count number (Akdeniz et al 2020 ; Omolaoye et al 2022 ). Also, it is worth mentioning that the mechanism of causing dysfunction in the reproduction system is remained a controversial issue since some studies stated that statins can improve the reproduction system and sperm quality (Abdulwahab et al 2021 ; Davis et al 2015 ; Sadeghi et al 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…Our data suggested hazardous effects of atorvastatin on the reproduction system which is in line with studies conducted on rat and human which reported erectile and testicular dysfunction, altered steroid hormone production, and reducing sperms’ count number (Akdeniz et al 2020 ; Omolaoye et al 2022 ). Also, it is worth mentioning that the mechanism of causing dysfunction in the reproduction system is remained a controversial issue since some studies stated that statins can improve the reproduction system and sperm quality (Abdulwahab et al 2021 ; Davis et al 2015 ; Sadeghi et al 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…Finally, statins have also been hypothesized to interfere with the spermatogenesis process [75] through their possible influence over the metabolism of cholesterol, which represents the main precursor of steroidal hormones. Cholesterol is also a determinant component of the plasma membrane of the sperm cell, where it certainly influences the protective and fusion capacity of the membrane itself [76].…”
Section: Discussionmentioning
confidence: 99%
“…Current HMGCR inhibitors in clinical use are mainly statins (Figure 3A; Table 3). Seven FDA-approved drugs include Lovastatin, Pravastatin, Simvastatin, Atorvastatin, Rosuvastatin, Pitavastatin, and Fluvastatin (Omolaoye et al, 2022). The first three inhibitors plus Mevastatin belong to the first generation of statins, derived from fungal products.…”
Section: Hmgcrmentioning
confidence: 99%